Towards Entrepreneurship: Reflections Between Theory And Practice - Benešová, Tereza (International Journal of Entrepreneurial Knowledge, 2015)
The paper deals with the pragmatic need of linking theory and practice in the learning process, focusing on vocational education in economics and entrepreneurship education. In connection with selected alternative economic theories is shown the necessity of praxeological educational background and practical work experience in teaching process in entrepreneurship education. Results are based on the research, which was done in the framework of prepared dissertation thesis on the theme of entrepreneurship education from the perspectives of theory and the perspective of vocational school teachers of economics subjects. The results focus on the concept of entrepreneurship education preferred by teachers of the economical subjects at the secondary schools specialised in economics. The main aim of the research was to check, to what degree are the theoretical bases of the education of the entrepreneurship fulfilled in the reality of a secondary school specialised in economics. The results show that in the case of preferred aims of the respondents of our examination we could talk about the combination of creation of knowledge and preparation for the profession. It is confirmed that the teachers rely significantly on a prescribed list of educational topics, but at the same time the results clearly show that the respondents think about their subject and formative aspect of their classes through using of cross-sectional topic.